In vitro antimicrobial susceptibility patterns of Propionibacterium acnes isolated from patients with acne vulgaris - Indu Biswal; Rajni Gaind; Neeraj Kumar; Srujana Mohanty; Vikas Manchanda; Niti Khunger; Ramesh V; Monorama Deb (Journal of Infection in Developing Countries)
Introduction: Propionibacterium acnes has been implicated in the development of acne vulgaris. Rampant use of topical and systemic antibiotics for acne vulgaris has led to resistance due to selective pressure. This study aimed to determine antibiotic resistance of P. acnes. Methodology: A total of 102 samples were collected from acne lesions and cultured onto sheep’s blood agar and brain-heart infusion agar supplemented with 5 g/L glucose and 2 mg/L furazolidone) (BHIg) under aerobic and anaerobic conditions. Species identification was done by conventional methods and the VITEK2 Compact system. The isolates were tested for penicillin, erythromycin, clindamycin, ciprofloxacin, nadifloxacin, and tetracycline by E-test, and minimum inhibitory concentration (MIC) of minocycline was determined by agar dilution on BHIg. MIC results were interpreted as per EUCAST (European Committee on Antimicrobial Susceptibility Testing) and CLSI (Clinical Laboratory Standards Institute) guidelines. Results: P. acnes was the most common anaerobe (66%) isolated. Resistance rates using EUCAST and CLSI breakpoints were 10.6% and 6.1%, 7.6% and 0%, 7.8% and 0% for erythromycin, clindamycin, and minocycline, respectively. Tetracycline resistance was observed in 9.2% isolates irrespective of the interpretative criteria used. MIC50 and MIC90 values for nadifloxacin (0.25 and 1 µg/mL) were found to be twofold lower than those for ciprofloxacin (0.5 and 1 µg/mL). Similarly, MIC50 and MIC90 values for minocycline (0.125 and 0.5 µg/mL) were also two- to threefold lower than those for tetracycline (0.38 and 1 µg/mL). Conclusions: To the best of our knowledge, this is the first study focusing on P. acnes resistance from India.